The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11999-009-1118-x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Displacement of the Tibia Increases in Deep Flexion of the Knee

Abstract: Background Deep knee flexion is important to proper function for some activities and in some cultures, although there are large posterior forces during high knee flexion. Most of what we know about posterior restraint and stability, however, has not been determined from deep flexion and without distinguishing motion in the medial and lateral compartments. Questions/purposes We therefore evaluated (1) the difference in posterior displacement between the medial and lateral compartments at a commonly used flexion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…However, during gait and running cycle, the knee was shown to rotate with respect to an axis that is located on the lateral side of the knee (Dyrby and Andriacchi, 2004; Hoshino and Tashman, 2012; Koo and Andriacchi, 2008; Kozanek et al, 2009), where Dyrby and Koo measured the kinematics of the knee during walking or leg extension using the motion analysis, Hoshino investigated the kinematics of the knee during running using CT 3D model and dynamic stereo X-ray system and Kozanek studied the kinematics of the knee during walking using the MRI 3D model and the dual fluoroscopy imaging system. These studies on various weight-bearing functions of the knee reported various patterns of the medial and lateral femoral condyle translations, which do not support the medial-pivoting description of the knee flexion (Fukagawa et al, 2010; Johal et al, 2005; Tanifuji et al, 2011). Instead, these data indicated that the kinematics is not uniform along the knee flexion path, especially during higher flexion, indicating that the knee kinematics is activity (or loading) dependent.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, during gait and running cycle, the knee was shown to rotate with respect to an axis that is located on the lateral side of the knee (Dyrby and Andriacchi, 2004; Hoshino and Tashman, 2012; Koo and Andriacchi, 2008; Kozanek et al, 2009), where Dyrby and Koo measured the kinematics of the knee during walking or leg extension using the motion analysis, Hoshino investigated the kinematics of the knee during running using CT 3D model and dynamic stereo X-ray system and Kozanek studied the kinematics of the knee during walking using the MRI 3D model and the dual fluoroscopy imaging system. These studies on various weight-bearing functions of the knee reported various patterns of the medial and lateral femoral condyle translations, which do not support the medial-pivoting description of the knee flexion (Fukagawa et al, 2010; Johal et al, 2005; Tanifuji et al, 2011). Instead, these data indicated that the kinematics is not uniform along the knee flexion path, especially during higher flexion, indicating that the knee kinematics is activity (or loading) dependent.…”
Section: Discussionmentioning
confidence: 83%
“…Many studies reported that during knee flexion, the translation of the femoral condyle with respect to tibial plateau is slightly towards posterior on medial side, whereas the lateral femoral condyle translated consistently in the posterior direction (Fukagawa et al, 2010; Johal et al, 2005; Tanifuji et al, 2011). This type of knee motion behavior has been referred to as a medial-pivoting rotation of the knee (Hill et al, 2000; Jensen, 2005; Johal et al, 2005; Tanifuji et al, 2011), where the knee axially rotates with respect to an axis located on the medial side of the knee during flexion (Johal et al, 2005; Tanifuji et al, 2011), Hill and Johal investigated the kinematics of the knee using open-MRI and Tanifuji used single-plane fluoroscopy during squatting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the healthy knee, the lateral tibiofemoral joint gap is significantly lax [17]. Posterior displacement with posterior stress was larger in the lateral compartment at 90° and 135° flexion [18]. Although achieving normal stability and kinematics in replaced knees is challenging, these kinematic data should be beneficial for designing high-flexion total knee prostheses.…”
Section: Resultsmentioning
confidence: 99%
“…Pivoting patterns of the intact healthy knee has been studied under different loading conditions. Medial‐pivoting pattern has been reported in non‐weight‐bearing seated positions, weight‐bearing squatting positions and during deep knee flexion in normal healthy subjects . This phenomenon has been attributed to the convex lateral and concave medial condyles of the normal tibial plateau.…”
Section: Discussionmentioning
confidence: 96%